Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/nu14061127
|View full text |Cite
|
Sign up to set email alerts
|

Added Fructose in Non-Alcoholic Fatty Liver Disease and in Metabolic Syndrome: A Narrative Review

Abstract: Non-alcoholic fatty liver disease (NAFLD) represents the most common chronic liver disease and it is considered the hepatic manifestation of metabolic syndrome (MetS). Diet represents the key element in NAFLD and MetS treatment, but some nutrients could play a role in their pathophysiology. Among these, fructose added to foods via high fructose corn syrup (HFCS) and sucrose might participate in NAFLD and MetS onset and progression. Fructose induces de novo lipogenesis (DNL), endoplasmic reticulum stress and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 76 publications
3
30
0
Order By: Relevance
“…Our results demonstrating the beneficial effect on the prognosis of cirrhotic patients of reducing the dietary intake of simple sugars, especially fructose, find support in data published in the field of NAFLD and MAFLD. Indeed, high fructose consumption exerts a negative metabolic effect in these patients on hepatic lipid synthesis, visceral adipose tissue accumulation, insulin resistance, increased uric acid and inflammation, and fibrosis progression [ 25 , 26 , 27 , 28 , 29 ]. Furthermore, it is known that patients with NAFLD and high amounts of visceral fat are at increased risk of insulin resistance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrating the beneficial effect on the prognosis of cirrhotic patients of reducing the dietary intake of simple sugars, especially fructose, find support in data published in the field of NAFLD and MAFLD. Indeed, high fructose consumption exerts a negative metabolic effect in these patients on hepatic lipid synthesis, visceral adipose tissue accumulation, insulin resistance, increased uric acid and inflammation, and fibrosis progression [ 25 , 26 , 27 , 28 , 29 ]. Furthermore, it is known that patients with NAFLD and high amounts of visceral fat are at increased risk of insulin resistance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, because patients with cirrhosis related to non-alcoholic fatty liver disease (NAFLD) or metabolic associated fatty liver disease (MAFLD) are steadily increasing overall and among LT candidates [ 19 , 20 , 21 , 22 , 23 , 24 ]. Secondly, because it is increasingly evident that in patients with NAFLD or MAFLD in the noncirrhotic phase, hepatic fat accumulation, inflammation, and hepatic fibrosis are associated with the consumption of simple sugars, in particular fructose and sucrose [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…While it is well established that NAFLD is associated with insulin resistance there is also evidence that specific components of the diet can contribute to its development. Animal [ 6 ] and human [ 7 , 8 , 24 ] studies have suggested that diets rich in fructose may promote hepatic steatosis and its progression to steatohepatitis, to a greater extent than glucose. Multiple mechanisms have been suggested for this response including direct effects on hepatic lipogenesis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review focuses on the impact of fructose and salt consumption on the development of hypertension, independent or preceding the full expression of metabolic syndrome, which may lead to heightened cardiovascular risk. The influence of fructose on metabolic syndrome is well recognized and reviewed in detail in several recent reviews [20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%